Therapeutic strategies for intracerebral hemorrhage - Li, Zhe; Khan, Suliman; Liu, Yang; Wei, Ruixue; Yong, V. Wee; Xue, Mengzhou (Frontiers in Neurology, 2022)
Stroke is the second highest cause of death globally, with an increasing incidence in developing countries. Intracerebral hemorrhage (ICH) accounts for 10–15% of all strokes. ICH is associated with poor neurological outcomes and high mortality due to the combination of primary and secondary injury. Fortunately, experimental therapies are available that may improve functional outcomes in patients with ICH. These therapies targeting secondary brain injury have attracted substantial attention in their translational potential. Here, we summarize recent advances in therapeutic strategies and directions for ICH and discuss the barriers and issues that need to be overcome to improve ICH prognosis.